Växtanvändning i krävande miljöer - Lövdahl, Magnus (2008)
Vegetation is a much appreciated element in our outdoor environment that has many advantages as well for the climate as for people's health. However in some types of environments vegetation may be problematic. Especially in urban areas with limited space, solid surfaces, pollutions, and warm and dry climate. In these environments vegetations may have difficulty surviving and moreover it may have a negative impact on the environment around it. It is also in these environments the most people are and so it is desirable to have as much vegetation as possible in these problematic environments. Therefore there is a need for knowledge of how we can integrate theses green elements in theses problematic environments in a sustainable and functional way. This can be done in several different ways. One way is to change the conditions of the environment so that the vegetation has better chances for development without having a negative impact on the environment. Another way is to choose species that are adapted to the environment they are to be planted in. In order to create sustainable and functional environments both these ways to work in has to be used. The purpose of the work that is presented in this paper is to make a contribution to a discussion about how we by choosing the right species for the right place may create more sustainable, functional and attractive environments. The paper is based on a short study of what five persons working in the green sector thinks about how to use vegetation in difficult environments. Based on the result of the study different aspects that effect how we work with vegetation and choice of spices for these more problematic environments.